Explaining High Unemployment in ECCU Countries - James, Ronald (IMF Working Papers; Working Paper ;, 2019)
In recent years, unemployment rates in some ECCU countries have been among the highest globally. This paper evaluates several factors that could explain them, finding that high unit labor costs, in a context of strong unionization, are significantly associated with high structural unemployment, while the global crisis added a cyclical component. Our analysis also suggests that high-paid jobs in the public and tourism sectors, which have been growing considerably in recent decades, could have increased the reservation wage and lowered labor force participation. We find no indication that high structural unemployment is related to the phase out of EU preferences on bananas/sugar exports or to a skills mismatch. As expected, unemployment has been substantially, but only temporarily fueled by large natural disasters.